Analisis Struktur Organisasi Sekretariat Dewan Perwakilan Rakyat Daerah Kabupaten Buleleng - Nyoman Ari Juru; Eddy Supriyadinata Gorda (Universitas Medan Area, 2021)
This study aims to analyze the duties and functions of the organizational structure of the regional legislative council secretariat of Buleleng Regency. This research used a qualitative descriptive approach which was conducted at the Secretariat of the Regional People's Representative Council of Buleleng Regency. The source of qualitative data was obtained through interviews with 8 informants, observations, and documents. Data analysis techniques used are data collection, data reduction, data presentation and conclusion drawing. The results of this study indicate that the factors that affect the duties and functions of the organizational structure of the local people's representative council secretariat in Buleleng Regency are matters that become regional authorities where the meaning of government affairs which is the authority of the region is regional apparatus which is only formed to carry out government affairs based on the principle of autonomy assistance tasks, apart from that those that affect the formulation of the organizational structure in Buleleng Regency are efficiency, effectiveness, division of tasks, span of control and flexibility. The secretariat of the regional people's representative council of Buleleng Regency with type A or large structure, in compiling the main tasks and structural functions organization refers to the goals of the organization and also the name of the position in the organizational structure, the disposition system or using a letter of assignment is used in assigning tasks that are not broken down into the duties and functions of the organizational structure.